2008
DOI: 10.2119/2007-00114.jouihan
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Mediated Inhibition of Mitochondrial Manganese Uptake Mediates Mitochondrial Dysfunction in a Mouse Model of Hemochromatosis

Abstract: Previous phenotyping of glucose homeostasis and insulin secretion in a mouse model of hereditary hemochromatosis (Hfe -/-) and iron overload suggested mitochondrial dysfunction. Mitochondria from Hfe -/-mouse liver exhibited decreased respiratory capacity and increased lipid peroxidation. Although the cytosol contained excess iron, Hfe -/-mitochondria contained normal iron but decreased copper, manganese, and zinc, associated with reduced activities of copper-dependent cytochrome c oxidase and manganese-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 56 publications
(55 reference statements)
6
67
0
Order By: Relevance
“…Since the Mn content was positively correlated with Mn-SOD activity in the cells, we assume that the increase of intracellular Mn is closely related to the activation of Mn-SOD. This concept may be supported by the observation that Mn supplementation increased Mn-SOD activity in mouse tissues [12]. In addition, we found that cellular Mn uptake was enhanced by asbestos exposure.…”
Section: Resultssupporting
confidence: 72%
“…Since the Mn content was positively correlated with Mn-SOD activity in the cells, we assume that the increase of intracellular Mn is closely related to the activation of Mn-SOD. This concept may be supported by the observation that Mn supplementation increased Mn-SOD activity in mouse tissues [12]. In addition, we found that cellular Mn uptake was enhanced by asbestos exposure.…”
Section: Resultssupporting
confidence: 72%
“…4a). In a model of hereditary hemochromatosis (Hfe –/– mice), hepatic iron overload was associated with an inhibition of mitochondrial manganese uptake and a reduced activity of MnSOD [57]. Furthermore, several yeast mutants with a high mitochondrial iron, and one mutant with low cellular manganese levels, all misincorporated iron instead of manganese into the MnSOD-active site [58].…”
Section: Discussionmentioning
confidence: 99%
“…The glutathione (GSH) and oxidized glutathione (GSSG) contents were measured with a specific glutathione assay kit to calculate the mitochondrial redox potential ( E h ) as previously described [26]. In addition, the activities of succinate dehydrogenase (SDH) and cytochrome c oxidase (COX) were quantified by measuring the slope of the absorbance curves [27]. …”
Section: Methodsmentioning
confidence: 99%